Post-Pandemic Library Era: Practices at Three Medical Libraries in Malaysia - Mejus, Levas; Mustapa, Nor Hasyimah; Mohd Nordin, Zuhanariah (2022)
COVID-19 has affected the way that libraries function, especially in terms of operations and services. Activities and stories shared in this paper show significant similarities amongst three medical university libraries in Malaysia, namely, the International Medical University (IMU) library in Kuala Lumpur, Newcastle University Medicine Malaysia (NUMed) library in Johor Bahru, and the Dar al-Hikmah International Islamic University Malaysia (IIUM) library in Kuantan, Pahang. These libraries were chosen due to several reasons ranging from mutual interest of the Library Heads where data can be easily retrieved within the capacity of the authors, similar categories of clientele served, and similar nature of courses offered. They experienced immediate changes in the way library services are provided and engagement of the users throughout this pandemic. The libraries were quick to adapt to changes and planned for activities to benefit the users with the limitations faced. As most academic libraries reopen and enter the endemic phase, a plan for more enhanced digital services is needed to ensure that the libraries are still supporting the pre- and post-pandemic teaching, learning, and research activities.